Understanding the Theoretical Foundations Underlying the Formalization of the Informal Economy - Nohoua, Traore (The journal of applied business and economics, 2023)
The objective of this article is to contribute to the deepening of knowledge on the theoretical foundations of formalization, based on a literature review in order to identify the paths of formalization. The present analysis shows that working in the informal sector is a rationally motivated decision of the entrepreneur. One of the solutions lies in the efficiency of the services provided by the State, given that the payment of taxes does not give the right to a simultaneous counterpart. It also shows that both the state and the entrepreneurs benefit from cooperation. Thus, their relations must be governed by a optimal contractual relationship for the successful formalisation. It has also been shown that micro-enterprises are subject to inadequate legislation, hence the need to revise the legislation in force. Also, the lack of support from the financial system and training programs adapted to the specificities of the enterprises would constitute fewer factors of production. Thus, it is desirable to improve the access of informal entrepreneurs to these productive resources.